Influence of Pb toxicity on yield, yield attributing parameters and photosynthetic pigment of tomato (Solanum lycopersicum) and eggplant (Solanum melongena) - GAUTAM, MAMTA; SINGH, ANIL KUMAR; JOHRI, RAJIV MOHAN (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted to evaluate the effect of Pb on yield and yield attributing parameters of tomato (Solanum lycopersicum L. cv Pusa Rohini) and eggplant (Solanum melongena L. cv Pusa Upkar). The photosynthetic pigment content and lead accumulation in both crops were also quantified. Tomato and eggplant crops were irrigated with waters having four concentrations of Pb (2.5, 5.0, 7.5 and 10 ppm). Normal water was used as control (0 ppm) in both the crops. Application of Pb contaminated irrigation water decreased plant height, leaf area/plant, number of fruits/plant, fresh fruit weight/plant, fruit yield/plant, dry weight/plant, above plant biomass/plant. The decrease ranged from 54% to 98% and 51% to 94% in tomato and eggplant, respectively, summarized for various parameters across treatments. The number of days to first fruit harvest increased by 1-2 days in 10 ppm treatment in both the crops. The inhibitory effects of photosynthetic pigments gradually increased with increase in concentration. 10 Pb ppm concentration resulted in the lowest pigment level (mg/g FW) and maximum inhibition rate compared to control. On the basis of the results obtained, it was concluded that tomato was more sensitive compared to eggplant. An attempt was also made to quantify the impact of Pb on the various parameters. The models used were linear, exponential, quadratic, and polynomial of degree 3. The responses could be described very satisfactorily by the polynomial of degree three with R2 > 99% for the both crops for all the parameters.